Techniques for evaluating the differences in multiregional input-output databases : a comparative evaluation of CO2 consumption-based accounts calculated using Eora, GTAP and WIOD /: a comparative evaluation of CO2 consumption-based accounts calculated using Eora, GTAP and WIOD. (2017) - Owen, Anne
No abstract available